Changes of inducible NO synthase and Interleukin-1β on the background of experimental rhegmatogenous retinal detachment - I. V. Savytskyi; G. V. Levytska; I. M. Levytskyi (Kazimierz Wielki University, 2018)
Purpose: inflammatory processes investigation in the rhegmatogenous retinal detachment pathogenesis and analysis of correction methods effectiveness. On the 7th day in experimental groups observed increase in the interleukin 1β level and inducible NOS activity. On 14th day of the research, as in the 7th, also confirms inflammatory process development. In addition to presence of statistically significant differences between iNOS and IL 1β indices of all experimental groups in comparison with the data of intact animals at the level of significance p